25 A study of the different methodologies used in calculation of extra-cellular volume by CMR imaging. (May 2018) - Vijapurapu, Ravi; Hawkins, Francesca; Liu, Boyang; Edwards, Nicola; Steeds, Richard
Abstract : Introduction: Tissue characterisation with MRI derived extra-cellular volume (ECV) measurement using T1 mapping is a well-recognised tool guiding clinical diagnosis and treatment. Concerns regarding blood-pool artefact have led to multiple methodologies with no consistency in assessment. This study investigates how ECV values and inter-observer reproducibility varies depending on technique. Methods: Patients with primary mitral regurgitation (MR) underwent multiparametric CMR imaging (1.5 T Siemens Avanto). ECV was calculated using MOLLI-derived T1 mapping (mid- and basal-LV, CircleCvi42) by two methods: global segmental analyses with variable endocardial:epicardial percentage offsets (20:20, 0:50, 10:50, 20:50) and region of interest (ROI). A second observer independently analysed a subset for inter-observer reproducibility, with independent exclusion of artefactual segments. Results: Thirty patients were studied (LVEF 72%±7%, LVEDVi 101±19 ml/m 2, LVESVi 30±11 ml/m 2, MR fraction 41%±16%, age 66±11 years). ECV values were lowest using ROI (septum 26.0%±2.5%, anterior 26.0%±0.26%, posterior 26.3%±0.39%), followed by 20:20 offset (28.0%±3.3%), and were highest with 0:50 offset (29.9%±3.4%). A 20:20 offset approach was most reproducible following 8% segmental exclusion (mean bias 0.21%±0.12%, intraclass correlation (ICC) 0.994), followed by 20:50, 10:50, and 0:50 offsets (mean bias 0.39%±0.24%, ICC 0.992). Anterior ROI was more reproducible than septal (mean bias 0.14%±0.72%, ICC 0.96 vs 0.48%±0.74%, ICC 0.929). Conclusion: There is considerable variability in ECV derived using ROI compared with a segmental approach, highlighting the importance of consistency within analyses. ECV calculation using septal ROI is commonly reported in the literature, but we have shown that a global segmental approach using 20:20 offsets have superior reproducibility, despite variable exclusion of artefactual segments.